NATURAL PHENOMENA AS CONCEPTUAL METAPHORS IN ENGLISH AND UZBEK: A COGNITIVE AND CROSS-CULTURAL ANALYSIS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the metaphorical conceptualization of natural phenomena in English and Uzbek from the perspective of cognitive linguistics. The study focuses on the role of natural elements such as water, fire, weather, and light as source domains for metaphorical expressions. Using a comparative approach, both universal patterns and culture-specific features are identified. The findings reveal the interconnection between language and cognition and highlight the influence of cultural worldview on metaphor formation.